Consensus report: faecal microbiota transfer – clinical applications and procedures. Issue 2 (27th November 2016) - König, J.; Siebenhaar, A.; Högenauer, C.; Arkkila, P.; Nieuwdorp, M.; Norén, T.; Ponsioen, C. Y.; Rosien, U.; Rossen, N. G.; Satokari, R.; Stallmach, A.; de Vos, W.; et al.
Summary: Background: Faecal microbiota transplantation or transfer (FMT) aims at replacing or reinforcing the gut microbiota of a patient with the microbiota from a healthy donor. Not many controlled or randomised studies have been published evaluating the use of FMT for other diseases than Clostridium difficile infection, making it difficult for clinicians to decide on a suitable indication. Aim: To provide an expert consensus on current clinical indications, applications and methodological aspects of FMT. Methods: Well‐acknowledged experts from various countries in Europe have contributed to this article. After literature review, consensus has been achieved by repetitive circulation of the statements and the full manuscript among all authors with intermittent adaptation to comments (using a modified Delphi process). Levels of evidence and agreement were rated according to the GRADE system. Consensus was defined a priori as agreement by at least 75% of the authors. Results: Key recommendations include the use of FMT in recurrent C. difficile infection characterised by at least two previous standard treatments without persistent cure, as well as its consideration in severe and severe‐complicated C. difficile infection as an alternative to total colectomy in case of early failure of antimicrobial therapy. FMT in inflammatory bowel diseases (IBD), irritable bowel syndrome (IBS) and metabolic syndrome should only be performed in research settings. Conclusions: Faecal microbiota transplantation or transfer is a promising treatment for a variety of diseases in which the intestinal microbiota is disturbed. For indications other than C. difficile infection, more evidence is needed before more concrete recommendations can be made.